Screening of the Ito Regulatory Subunit Klf15 in Patients with Early-Onset Lone Atrial Fibrillation - Nielsen, Morten W.; Olesen, Morten S.; Refsgaard, Lena; Haunso, Stig; Svendsen, Jesper H. (Frontiers in Genetics, 2013)
Several studies have associated mutations in genes encoding potassium channels and accessory subunits involved in cardiac repolarisation with susceptibility of atrial fibrillation (AF). Recently, the krüppel-like factor 15 (Klf15) was found to transcriptionally control rhythmic expression of KChIP2, a critical subunit required for generating the transient outward potassium current (Ito), and that deficiency or excess of Klf15 increased susceptibility of arrhythmias. On this basis we hypothesized that mutations in Klf15 could be associated with susceptibility of AF. A total of 209 unrelated Caucasian lone AF patients were screened for mutations in KLF15 by direct sequencing. No mutations in the lone AF cohort were found. In one patient we found a synonymous variant (c.36C>T). In NHLBI GO Exome Sequencing Project (ESP) the variant was present in 31 of 4269 Caucasian individuals and in 3 of 2200 African Americans. In our cohort KLF15 were not associated with lone AF.